Loofah sponge loaded nano zero-valent iron material, preparation method and application of loofah sponge loaded nano zero-valent iron material in degradation of tetrabromobisphenol A
By using loofah-loaded nano-zero-valent iron materials, the problem of nano-zero-valent iron being easily deactivated and agglomerated in wastewater treatment is solved, and the effect of efficient degradation of tetrabromobenzene A is achieved, and good reusability and low energy consumption are achieved.
Patent Information
- Application Number
- CN202510036482.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-03-04
AI Technical Summary
Existing nano zero-valent iron is prone to deactivation and agglomeration in wastewater treatment, affecting reaction activity and selectivity, and has high energy consumption for high temperature calcination or secondary pollution of the reaction by-products of vulcanizing agents.
The loofah is used as a carrier, and the mixture of alkali solution, hydrogen peroxide and acetic acid solution, ultrasonic and stirring treatment, and reducing agent solution treatment, were prepared to carry nano zero-valent iron materials, avoiding the agglomeration of nano zero-valent iron, and improving its dispersion and active site utilization.
The produced loofah-loaded nano zero-valent iron material has high mechanical strength, good reusability and high specific surface area, and can effectively degrade tetrabromobenzene A, with simple steps, mild conditions and low energy consumption.
Smart Images

Figure CN119549125A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of pollutant treatment, and in particular to a loofah-loaded nano zero-valent iron material, a preparation method and application thereof in degrading tetrabromobisphenol A. Background Art
[0002] Tetrabromobisphenol A (TBBPA) is the brominated flame retardant with the largest production and usage volume, and can be used in products such as plastics, rubber, and textiles. TBBPA has been proven to have potential carcinogenic risks, and also exhibits multiple harmful effects such as cell and neurotoxicity and endocrine disruption effects. It can be discharged into environmental media during production, processing, use, and waste disposal. TBBPA has been detected in water, soil, sludge, and atmospheric dust. TBBPA is discharged into the environment with wastewater, which will pose a threat to the safety of receiving water bodies and affect ecosystems and human health.
[0003] Nano-zero-valent iron has the advantages of high reactivity, small size, high surface energy, and large specific surface area. It has excellent effects in removing pollutants, is easy to prepare, and has low cost. It has broad application prospects in sewage treatment. However, in practical applications, nano-zero-valent iron is easy to deactivate and agglomerate, which affects the reactivity, selectivity, and electron mobility. It is also difficult to recycle, which limits its further large-scale application.
[0004] Loading nano zero-valent iron onto a suitable carrier is an effective means to solve this problem. Researchers have conducted in-depth research on this. For example, the Chinese patent document with publication number CN111097414A discloses a simple method for loading ultrafine nano zero-valent iron onto porous materials. The invention mixes organic iron salts, organic ligands and porous materials, and then carbonizes them at high temperature under the protection of inert gas, so that ultrafine zero-valent iron can be evenly loaded onto the inner and outer surfaces and pores of the porous material. The Chinese patent document with publication number CN115070029A discloses a carbon-based loaded sulfide nano zero-valent iron and its preparation method and application. The carbon-based loaded sulfide nano zero-valent iron includes biochar with a porous structure and sulfide nano zero-valent iron loaded on the surface and pores of the biochar. The sulfide nano zero-valent iron nanoparticles are core-shell structures, with nano zero-valent iron as the core and sulfide as the shell. A Chinese patent document with publication number CN110980858A discloses a method for removing halogenated organic matter in sewage using biochar-loaded nano-sulfide zero-valent iron material. The preparation method of the biochar-loaded nano-sulfide zero-valent iron material includes: mixing biomass and FeSO4 solution under vacuum or inert atmosphere, evaporating, grinding, and drying to obtain FeSO4-loaded biomass; and pyrolyzing the FeSO4-loaded biomass at 800-1000°C under an inert atmosphere to obtain the obtained biomass.
[0005] Although the above method successfully achieves the loading of nano zero-valent iron, there are problems of high energy consumption of high-temperature calcination during the loading process, or secondary pollution problems caused by by-products of the sulfiding agent reaction. Summary of the invention
[0006] In order to solve the shortcomings of the prior art, the present invention provides a method for preparing a loofah-loaded nano zero-valent iron material, which has simple steps and mild conditions. The prepared loofah-loaded nano zero-valent iron material has a large specific surface area, high mechanical strength, and good reusability, and has broad application prospects in the degradation of tetrabromobisphenol A.
[0007] The specific technical solutions adopted are as follows:
[0008] A method for preparing a loofah-loaded nanometer zero-valent iron material comprises the following steps:
[0009] (1) utilize the alkali liquor treatment loofah of 2wt%-6wt%, place hydrogen peroxide and acetic acid mixed solution after alkali liquor treatment loofah, heated and stirred, washing, drying, complete the pre-treatment of loofah;
[0010] (2) placing the pretreated loofah in a metal ion solution under an oxygen-isolating environment, performing ultrasonic and stirring treatment, and further vacuum impregnation; the metal ions include ferric ions or ferrous ions;
[0011] (3) In an oxygen-proof environment, placing the loofah obtained in step (2) in a reducing agent solution, wherein the reducing agent is sodium borohydride or potassium borohydride, stirring the reaction until no bubbles are generated, washing and drying to obtain the loofah-loaded nano zero-valent iron material.
[0012] The present invention performs alkali washing on the loofah to remove substances such as pectin. The loofah is mainly composed of cellulose, hemicellulose and lignin in terms of material properties. The three components have a tight structure, so that the hydroxyl groups on the molecules cannot be exposed. Therefore, some methods are needed to loosen them to a certain extent, thereby changing the tight combination between the three components, exposing the groups, and being conducive to the reaction. Hydrogen peroxide and acetic acid are selected to prepare peracetic acid in situ, and lignin is selectively removed by using its strong oxidizing property. At the same time, hydrogen peroxide can oxidize some functional groups (such as phenolic hydroxyl groups) in lignin into more active functional groups (such as quinone structures), improve the performance of the loofah, and improve its adsorption capacity for divalent iron ions or trivalent iron ions. The pretreated loofah maintains the original three-dimensional porous structure, and the active groups are exposed to the outside. Functional groups such as carboxyl and hydroxyl groups are easy to combine with iron ions or ferrous ions. After the iron ions or ferrous ions are loaded, nano zero-valent iron is further prepared by the action of a reducing agent, avoiding the agglomeration of nano zero-valent iron, improving the dispersibility of nano zero-valent iron, and greatly increasing the utilization rate of active sites. At the same time, nickel ions, copper ions, palladium ions, cobalt ions, etc. are added to form a bimetallic agent and loaded on the loofah, which can also improve the degradation effect of the system of the present invention on tetrabromobisphenol A.
[0013] Specifically, in step (1), the alkali solution is a sodium hydroxide solution or a potassium hydroxide solution, and the alkali solution treatment time is 30-90 minutes.
[0014] Preferably, in step (1), the mixed solution of hydrogen peroxide and acetic acid is obtained by mixing equal volumes of 10%-30% hydrogen peroxide solution and 80%-100% acetic acid solution.
[0015] More preferably, the temperature of heating and stirring is 40-65° C. for 8-10 hours. Failure to heat will result in incomplete modification of the loofah, while too high a temperature or too long a time will damage the structure of the loofah and reduce its mechanical strength.
[0016] Preferably, in the metal ion solution of step (2), the concentration of metal ions is 0.002-5 mol / L, further 0.075-0.5 mol / L; the ultrasonic time is 5-20 min; and the stirring time is 2-6 h.
[0017] More preferably, the metal ions further include one of nickel ions, copper ions, palladium ions or cobalt ions. The formation of bimetallics can improve the degradation effect of the loofah-loaded nano zero-valent iron material on tetrabromobisphenol A.
[0018] Further preferably, the mass ratio of the pretreated loofah to the metal ion solution is 1:50-200.
[0019] Preferably, the vacuum impregnation temperature is 20-35° C. and the time is 2-4 h.
[0020] Preferably, the concentration of the reducing agent solution in step (3) is 0.002-5 mol / L, further 0.15-1.5 mol / L.
[0021] The present invention also provides a loofah-loaded nano zero-valent iron material prepared by the preparation method of the loofah-loaded nano zero-valent iron material. The loofah is light in weight and still maintains a three-dimensional porous structure and excellent mechanical properties after pretreatment. The nano zero-valent iron is loaded therein, which not only reduces the burden of loofah waste on the environment, but also solves the problem of easy agglomeration of nano zero-valent iron.
[0022] The loofah-loaded nano zero-valent iron material has high mechanical strength and good recycling effect.
[0023] The invention also provides application of the loofah-loaded nanometer zero-valent iron material in degrading tetrabromobisphenol A.
[0024] The invention also provides a method for treating wastewater containing tetrabromobisphenol A, and utilizes the loofah-loaded nano zero-valent iron material to degrade tetrabromobisphenol A.
[0025] Specifically, the loofah-loaded nano zero-valent iron material is placed in wastewater containing tetrabromobisphenol A to react and degrade the tetrabromobisphenol A.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] (1) The method of the present invention uses loofah as a raw material. The loofah has a loose and porous structure and a large specific surface area. After pretreatment, its three-dimensional porous structure is still maintained, and the carboxyl and hydroxyl groups exposed on the surface are easy to combine with iron ions or ferrous ions, and the loofah-loaded nano zero-valent iron material is prepared by reduction. The method of the present invention reduces the burden of loofah waste on the environment, and can also "treat waste with waste" and utilize loofah as waste.
[0028] (2) The loofah-loaded nano-zero-valent iron material prepared by the method of the present invention can effectively fix the nano-zero-valent iron, prevent its agglomeration, increase the utilization rate of active sites, and has high mechanical strength and is easy to separate solid from liquid and recover, so that it can be reused and has good reusability.
[0029] (3) The method of the present invention has simple steps, mild reaction conditions, low energy consumption, and is easy to implement. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is an optical picture of loofah raw materials.
[0031] Figure 2 This is an optical picture of the loofah after pretreatment in Example 2.
[0032] Figure 3 This is an optical picture of the loofah-loaded nano zero-valent iron material prepared in Example 2.
[0033] Figure 4 This is an optical picture of nano zero-valent iron in Comparative Example 1.
[0034] Figure 5 This is a diagram showing the effect of degrading tetrabromobisphenol A by the loofah-loaded nano zero-valent iron samples in Examples 1-4 and the samples in Comparative Examples 1 and 2.
[0035] Figure 6 This is a diagram showing the effect of repeated use of the loofah-loaded nano zero-valent iron material prepared in Example 2. DETAILED DESCRIPTION
[0036] In order to make the purpose, features and advantages of the present invention more obvious and easy to understand, the following is a detailed description through specific embodiments. In the following description, many specific details are set forth in order to fully understand the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below. The technical features in each embodiment of the present invention can be combined accordingly without conflicting with each other.
[0037] The operating methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or according to the conditions recommended by the manufacturer. The contents not described in detail in this specification belong to the prior art known to professionals in the field. The experimental materials used in the following examples, unless otherwise specified, can be purchased from conventional biochemical reagent companies.
[0038] Example 1
[0039] Step 1, cut the loofah into 1cm*1cm pieces, add it into 2wt% NaOH solution, soak and stir for 60min, wash it with deionized water until neutral, and dry it at 60℃ for 12h;
[0040] Step 2, adding the alkali-treated loofah to a mixed solution of hydrogen peroxide and acetic acid (30% hydrogen peroxide and 99% acetic acid solution mixed in a volume ratio of 1:1), heating and stirring at 60° C. for 8 h, washing with deionized water until neutral, and drying at 60° C. to obtain a pretreated loofah;
[0041] Step 3, adding 4.1703 g of ferrous sulfate heptahydrate into 150 mL of deoxygenated water and stirring to dissolve to obtain a ferrous sulfate solution, adding 0.84 g of the pretreated loofah sponge therein, first ultrasonically treating for 15 min, then stirring for 2 h, and further vacuum impregnating at 30 ° C for 3 h;
[0042] Step 4: Weigh 1.5132 g of sodium borohydride and add it to 200 mL of deoxygenated water to dissolve to obtain a reducing agent solution. Under a nitrogen atmosphere, place the loofah obtained in step 3 in the reducing agent solution and stir until no bubbles are generated. Quickly wash the reacted loofah with deoxygenated water and anhydrous ethanol several times, and then place it in a vacuum drying oven at 50°C and dry it for 24 hours to obtain a loofah-loaded nano zero-valent iron material.
[0043] Taking tetrabromobisphenol A as the target degradation product, 0.42g of loofah-loaded nano zero-valent iron material was weighed and added to 100mL of 5mg / L tetrabromobisphenol A solution. The entire reaction process was carried out in a nitrogen atmosphere. The reaction was shaken at 200r / min at 30°C in a constant temperature reactor for 10 hours. Samples were taken at fixed times, and the concentration of tetrabromobisphenol A was determined by HPLC, and the removal efficiency was calculated.
[0044] Example 2
[0045] Step 1, cut the loofah into 1cm*1cm pieces, add it into 2wt% NaOH solution, soak and stir for 40min, wash it with deionized water until neutral, and dry it at 60℃ for 12h;
[0046] Step 2, adding the alkali-treated loofah to a mixed solution of hydrogen peroxide and acetic acid (30% hydrogen peroxide and 99% acetic acid solution mixed in a volume ratio of 1:1), heating and stirring at 60° C. for 10 h, washing with deionized water until neutral, and drying at 60° C. to obtain a pretreated loofah;
[0047] Step 3, adding 4.1703 g of ferrous sulfate heptahydrate into 150 mL of deoxygenated water and stirring to dissolve to obtain a ferrous sulfate solution, adding 0.42 g of the pretreated loofah sponge therein, first ultrasonically treating for 15 min, then stirring for 2 h, and further vacuum impregnating at 30 ° C for 2 h;
[0048] Step 4: Weigh 1.5132 g of sodium borohydride and add it to 200 mL of deoxygenated water to dissolve to obtain a reducing agent solution. Under a nitrogen atmosphere, place the loofah obtained in step 3 in the reducing agent solution and stir until no bubbles are generated. Quickly wash the reacted loofah with deoxygenated water and anhydrous ethanol several times, and then place it in a vacuum drying oven at 50°C and dry it for 24 hours to obtain a loofah-loaded nano zero-valent iron material.
[0049] Taking tetrabromobisphenol A as the target degradation product, 0.42g of loofah-loaded nano zero-valent iron material was weighed and added to 100mL of 5mg / L tetrabromobisphenol A solution. The entire reaction process was carried out in a nitrogen atmosphere. The reaction was shaken at 200r / min at 30°C in a constant temperature reactor for 10 hours. Samples were taken at fixed times, and the concentration of tetrabromobisphenol A was determined by HPLC, and the removal efficiency was calculated.
[0050] Example 3
[0051] Step 1, cut the loofah into 1cm*1cm pieces, add it into 4wt% NaOH solution, soak and stir for 30min, wash it with deionized water until it is neutral, and dry it at 60℃ for 12h;
[0052] Step 2, adding the alkali-treated loofah to a mixed solution of hydrogen peroxide and acetic acid (30% hydrogen peroxide and 99% acetic acid solution mixed in a volume ratio of 1:1), heating and stirring at 60° C. for 10 h, washing with deionized water until neutral, and drying at 60° C. to obtain a pretreated loofah;
[0053] Step 3, adding 4.1703 g of ferrous sulfate heptahydrate into 150 mL of deoxygenated water and stirring to dissolve to obtain a ferrous sulfate solution, adding 2.52 g of the pretreated loofah sponge therein, first ultrasonically treating for 15 min, then stirring for 2 h, and further vacuum impregnating at 30 ° C for 2 h;
[0054] Step 4: Weigh 1.5132 g of sodium borohydride and add it to 200 mL of deoxygenated water to dissolve to obtain a reducing agent solution. Under a nitrogen atmosphere, place the loofah obtained in step 3 in the reducing agent solution and stir until no bubbles are generated. Quickly wash the reacted loofah with deoxygenated water and anhydrous ethanol several times, and then place it in a vacuum drying oven at 50°C and dry it for 24 hours to obtain a loofah-loaded nano zero-valent iron material.
[0055] Taking tetrabromobisphenol A as the target degradation product, 0.42g of loofah-loaded nano zero-valent iron material was weighed and added to 100mL of 5mg / L tetrabromobisphenol A solution. The entire reaction process was carried out in a nitrogen atmosphere. The reaction was shaken at 200r / min at 30°C in a constant temperature reactor for 10 hours. Samples were taken at fixed times, and the concentration of tetrabromobisphenol A was determined by HPLC, and the removal efficiency was calculated.
[0056] Example 4
[0057] The preparation method of the loofah loaded nano zero-valent iron material in this embodiment is the same as that in Example 1, with the only difference being that in step 3, a mixed solution of ferrous sulfate and copper sulfate is prepared, the concentration of ferrous ions in the mixed solution is 0.15 mol / L, and the concentration of copper ions is 0.075 mol / L, and the pretreated loofah is placed therein; the other processes and parameters are the same as those in Example 1, and a loofah loaded copper-nano zero-valent iron material is obtained.
[0058] Example 5
[0059] The preparation method of the loofah-loaded nano zero-valent iron material in this embodiment is the same as that in Example 1, except that ferric chloride is used instead of ferrous sulfate, and the concentration of iron ions is maintained at 0.1 mol / L. Other processes and parameters are the same as those in Example 1.
[0060] Example 6
[0061] The preparation method of the loofah-loaded nano zero-valent iron material in this embodiment is the same as that in Example 1, except that potassium borohydride is used instead of sodium borohydride, and the concentration of the reducing agent is maintained at 0.2 mol / L. Other processes and parameters are the same as those in Example 1.
[0062] Comparative Example 1
[0063] Step 1: Weigh 4.4483 g of ferrous sulfate heptahydrate, add it into 80 mL of deoxygenated water, stir and dissolve it to obtain a ferrous sulfate solution; weigh 1.2105 g of sodium borohydride, add it into 150 mL of deoxygenated water, stir and dissolve it to obtain a reducing agent solution.
[0064] Step 2: Slowly drip the ferrous sulfate solution into the reducing agent solution at a rate of 2 mL / min. The entire reaction process is carried out under a nitrogen atmosphere. Stir for 1 hour to generate a black precipitate. The obtained product is washed with deoxygenated water and anhydrous ethanol for multiple times, and dried in a vacuum drying oven at 55° C. for 24 hours to obtain nano zero-valent iron.
[0065] Taking tetrabromobisphenol A as the target degradation product, about 0.12g (8 times the iron content of the loofah-loaded nano zero-valent iron material prepared in Example 2) of nano zero-valent iron was weighed and added to 100mL of 5mg / L tetrabromobisphenol A solution. The entire reaction process was carried out in a nitrogen atmosphere. The reaction was shaken at 200r / min at 30°C in a constant temperature reactor for 10 hours. Samples were taken at fixed times, and the concentration of tetrabromobisphenol A was determined by high performance liquid chromatography, and the removal efficiency was calculated.
[0066] Comparative Example 2
[0067] The preparation method of the loofah-loaded nano zero-valent iron material in this comparative example is the same as that in Example 1, except that the operation of treating with a mixed solution of hydrogen peroxide and acetic acid in step 2 is not performed, and other processes and parameters are the same as those in Example 1.
[0068] Sample analysis
[0069] Optical pictures of loofah raw materials Figure 1 As shown, the optical image of nano zero-valent iron in Comparative Example 1 is as follows Figure 4 As shown, the optical image of the loofah after pretreatment in Example 2 is as follows Figure 2 As shown, the pretreated loofah has removed most of the lignin and turned white. The optical image of the loofah loaded with nano zero-valent iron material prepared in Example 2 is as shown in FIG. Figure 3 As shown, it can be seen that nano zero-valent iron is evenly loaded on the loofah, and the agglomeration problem of magnetic nanoparticles is improved.
[0070] The effect of the loofah loaded nano zero-valent iron samples in Examples 1-4 and the samples in Comparative Examples 1 and 2 on the degradation of tetrabromobisphenol A is shown in the figure below. Figure 5 As shown, after 10 hours of reaction, the degradation efficiency of tetrabromobisphenol A in comparative examples 1 and 2 reached 50% and 46%, respectively, and the degradation efficiency of tetrabromobisphenol A in the loofah loaded with nano zero-valent iron material prepared in Examples 1-3 was 88%, 100%, and 77%, respectively. It can be seen that Examples 1-3 are all higher in degradation efficiency of tetrabromobisphenol A than Comparative Examples 1 and 2, indicating that the pretreated loofah effectively improves the adsorption capacity of loofah for iron ions or ferrous ions; at the same time, the loofah loaded with nano zero-valent iron material effectively fixes the nano zero-valent iron, reduces agglomeration, and increases the utilization rate of active sites. In Example 4, copper is added to form a bimetallic load on the loofah. Compared with Example 1, the degradation efficiency of tetrabromobisphenol A is also improved, reaching 94%.
[0071] After the degradation test, the composite material of Example 2 was collected by magnet, and then multiple tests were performed. The collected loofah-loaded nano zero-valent iron material was washed with ultrapure water until neutral, and then dried at 60°C for 12 hours after centrifugation. The dried material was weighed for the next test, and the recycling performance and stability of the material were evaluated according to the degradation of tetrabromobisphenol A. The results are shown in FIG. Figure 6 As shown. It can be seen that with the increase of the number of cycles, the degradation efficiency of tetrabromobisphenol A does not decrease significantly. After 5 cycles, its degradation efficiency can still reach 78%. It can be seen that the loofah-loaded nano zero-valent iron material of the present invention can be reused many times and has excellent recycling ability.
[0072] The embodiments described above provide a detailed description of the technical solutions of the present invention. It should be understood that the above are only specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, supplements or similar substitutions made within the scope of the principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a loofah-loaded nanometer zero-valent iron material, characterized in that: The following steps are involved: (1) utilize the alkali liquor treatment loofah of 2wt%-6wt%, place hydrogen peroxide and acetic acid mixed solution after alkali liquor treatment loofah, heated and stirred, washing, drying, complete the pre-treatment of loofah; (2) placing the pretreated loofah in a metal ion solution under an oxygen-isolating environment, performing ultrasonic and stirring treatment, and further vacuum impregnation; the metal ions include ferric ions or ferrous ions; (3) In an oxygen-proof environment, placing the loofah obtained in step (2) in a reducing agent solution, wherein the reducing agent is sodium borohydride or potassium borohydride, stirring the reaction until no bubbles are generated, washing and drying to obtain the loofah-loaded nano zero-valent iron material.
2. The method for preparing the loofah-loaded nanometer zero-valent iron material according to claim 1, wherein: In step (1), the alkali solution is a sodium hydroxide solution or a potassium hydroxide solution, and the alkali solution treatment time is 30-90 minutes.
3. The preparation method of loofah-loaded nano zero-valent iron material according to claim 1, characterized in that, In step (1), the hydrogen peroxide and acetic acid mixed solution is obtained by mixing equal volumes of 10%-30% hydrogen peroxide solution and 80%-100% acetic acid solution.
4. The method for preparing the loofah-loaded nanometer zero-valent iron material according to claim 3, wherein: The heating and stirring temperature is 40-65°C for 8-10h.
5. The method for preparing the loofah-loaded nanometer zero-valent iron material according to claim 1, wherein: In the metal ion solution of step (2), the concentration of metal ions is 0.002-5 mol / L; the ultrasonic time is 5-20 min; and the stirring time is 2-6 h.
6. The method for preparing the loofah-loaded nanometer zero-valent iron material according to claim 1, characterized in that: The metal ion also includes one of nickel ion, copper ion, palladium ion or cobalt ion.
7. The method for preparing the loofah-loaded nanometer zero-valent iron material according to claim 1, characterized in that: The concentration of the reducing agent solution in step (3) is 0.002-5 mol / L.
8. The loofah-loaded nano zero-valent iron material obtained according to the preparation method of the loofah-loaded nano zero-valent iron material according to any one of claims 1 to 7.
9. Use of the loofah-loaded nano zero-valent iron material according to claim 8 in the degradation of tetrabromobisphenol A.
10. A method for treating wastewater containing tetrabromobisphenol A, characterized in that: Tetrabromobisphenol A is degraded using the loofah-loaded nano zero-valent iron material described in claim 8.
Citation Information
Patent Citations
Preparation method and application of biochar-loaded nano zero-valent iron sulfide material
CN110980858A
Simple method for loading ultrafine nano zero-valent iron on porous material
CN111097414A
Carbon-based supported vulcanized nano zero-valent iron as well as preparation method and application thereof
CN115070029A